(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Polyalthia simiarum (Hook. F. &Thomson) exhibits different effects in human body. Objective: As a part of ongoing research on medicinal plants of Bangladesh, the present study is focused to investigate the analgesic and anti-inflammatory activities of stem bark of Polyalthia simiarum (Annonaceae). Methodology: The ethyl acetate (EA) and petroleum ether (PE) extracts were subjected to qualitative chemical investigation for the identification of different phytoconstituents. The analgesic activity was determined for its central and peripheral pharmacological actions using tail immersion method and acetic acid-induced writhing test. The anti-inflammatory activity was evaluated by carrageenan induced paw edema in rats. Analgesic and anti-inflammatory data were evaluated statistically analysed by Dunnett’s-T test. Result: Both extracts at the dose of 50- and 100 mg/kg b.w., produced significant increase in pain threshold in tail immersion method whereas significantly reduced the writhing caused by acetic acid in a dose dependent manner. The EA and PE extracts showed anti-inflammatory activities at 50- and 100 mg/kg body weight. Among all the extracts, the EA extract showed a dose dependent and comparable analgesic activity in all the tested methods and also reduced the paw edema considerably (27.5% and 39.1% inhibition after 4h), in dose dependent manner when compared to carrageenan induced control rat. Conclusion: Therefore, the EA and PE extracts of Polyalthia simiarum were capable to exhibit moderate analgesic and anti-inflammatory activities. This is the first report of analgesic and anti-inflammatory potential of Polyalthia simiarum and can be further investigated to isolate the active compounds responsible for the biological activities. Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 18-23